Analysis of Liquid Migration as a Manifestation of Migration-based Lifestyle in the Third Millennium Using a Qualitative Approach - Ebrahim Mohammadpour; Tavakkol Aghayari Hir; Hacı Duran; Mohammad Abbaszadeh (Journal of Economy Culture and Society)
Immigration, as a social phenomenon, has always held a significant place in the sociology literature. The migration phenomenon has been extensively studied within the scope of industrialization, urbanization, wars, and global development challenges. However, contemporary consumer society values, globalization, and ongoing social crises have added new dimensions to migration. Hyperreality images, fluid society values, advancements in communication technologies, and evolving work environments have transformed migration into a way of life. Recent research has increasingly focused on these aspects. This study operates under the assumption that migration engenders a unique lifestyle. In this study, liquid migration is explored as a manifestation of the migration-based lifestyle of the third millennium. This study employed a mixed methodological approach. For the quantitative component, 116 students from Tabriz University were selected by random sampling. Drawing from previous studies, six factors (economic, social, educational, environmental, political, and demographic) were assessed. The quantitative results indicated that according to Tabriz University students, economic and educational motives rank highest among the factors influencing the desire to migrate. Moreover, a significant and positive correlation was observed among the six migration-influencing factors. This study contributes to the growing body of literature on migration by shedding light on the evolving nature of migration as a lifestyle choice, particularly in the contemporary context of fluid societal values and global interconnectedness.